Nutrient Uptake and Chlorophyll of Long Bean Plants (Vigna Sinensis L.) Due to Liquid Waste Tofu and Planting Media: Serapan Hara Dan Klorofil Tanaman Kacang Panjang (Vigna Sinensis L.) Akibat Pemberian Limbah Cair Tahu Dan Media Tanam - Nindi Fauziah; M. Idris; Rahmadina (Talenta Publisher, 2022)
This study aims to determine the absorption of nutrients N, P, total chlorophyll, and combination interactions due to the application of tofu liquid waste and growing media to long beans. The study used a factorial randomized block design (RBD) with 3 replications. Factor I of tofu liquid waste treatment (T) consisted of 3 levels, namely: T0 (0 ml), T1 (150 ml), T2 (300 ml ), and Factor II , Growing Media (M) consisted of 3 planting media, namely M1 (compost of cow dung + rice husk charcoal), M2 (compost of cow dung + cocopeat), and M3 (compost of cow dung + chopped fern). The observed variables included nutrient uptake of N-Total, P, and total chlorophyll content. The results showed that the treatment of tofu liquid waste had a very significant effect on N-Total and P nutrient uptake, namely 150 ml (T1) and the administration of 300 ml (T2) had a very significant effect on total chlorophyll content. The growing media had a very significant effect on nutrient uptake of N, P, and total chlorophyll content in the M3 treatment( cow manure compost + chopped fern). There was no interaction between tofu liquid waste and planting media for all observed variables